Women and Trade : The Role of Trade in Promoting Gender Equality - World Bank; World Trade Organization (Washington, DC: World Bank, 2020)
Trade can dramatically improve women’s lives, creating new jobs, enhancing consumer choices, and increasing women’s bargaining power in society. It can also lead to job losses and a concentration of work in low-skilled employment. Given the complexity and specificity of the relationship between trade and gender, it is essential to assess the potential impact of trade policy on both women and men and to develop appropriate, evidence-based policies to ensure that trade helps to enhance opportunities for all. Research on gender equality and trade has been constrained by limited data and a lack of understanding of the connections among the economic roles that women play as workers, consumers, and decision makers. Building on new analyses and new sex-disaggregated data, Women and Trade: The Role of Trade in Promoting Gender Equality aims to advance the understanding of the relationship between trade and gender equality and to identify a series of opportunities through which trade can improve the lives of women.